2020
DOI: 10.3390/ijms21031092
|View full text |Cite
|
Sign up to set email alerts
|

Displaced Myonuclei in Cancer Cachexia Suggest Altered Innervation

Abstract: An idiopathic myopathy characterized by central nuclei in muscle fibers, a hallmark of muscle regeneration, has been observed in cancer patients. In cancer cachexia skeletal muscle is incapable of regeneration, consequently, this observation remains unaccounted for. In C26-tumor bearing, cachectic mice, we observed muscle fibers with central nuclei in the absence of molecular markers of bona fide regeneration. These clustered, non-peripheral nuclei were present in NCAM-expressing muscle fibers. Since NCAM expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 58 publications
3
25
0
Order By: Relevance
“…155 Although less convincing, fairly similar observations were also reported in skeletal muscle of cancer cachectic patients compared with non-weight-losing cancer patients and control subjects. 155 However, a recent study showed that neuromuscular junction morphology and structural integrity are conserved between control subjects, weight-stable cancer patients, and cachectic cancer patients. 156 Although a molecular characterization of denervation markers was not performed in this study, the absence of neuromuscular junction pathology is in contrast to what is found in the aforementioned study in cachectic C26 tumour-bearing mice.…”
Section: Skeletal Muscle Atrophy and Chemotherapymentioning
confidence: 77%
See 1 more Smart Citation
“…155 Although less convincing, fairly similar observations were also reported in skeletal muscle of cancer cachectic patients compared with non-weight-losing cancer patients and control subjects. 155 However, a recent study showed that neuromuscular junction morphology and structural integrity are conserved between control subjects, weight-stable cancer patients, and cachectic cancer patients. 156 Although a molecular characterization of denervation markers was not performed in this study, the absence of neuromuscular junction pathology is in contrast to what is found in the aforementioned study in cachectic C26 tumour-bearing mice.…”
Section: Skeletal Muscle Atrophy and Chemotherapymentioning
confidence: 77%
“…167 However, this concept has recently been questioned at least in C26 tumour-bearing mice. 155 Anyhow, an in-depth analysis of skeletal muscle junction and neuromuscular coupling is necessary for cancer patients and animal models of cancer cachexia. Loss in muscle force can also result from impairment in calcium handling.…”
Section: Potential Factors Involved In Muscle Force Decreasementioning
confidence: 99%
“…11 Shortened myonuclei in PoWeR-trained muscle fibres and elongated myonuclei in 6-month detrained muscle fibres could be a response to a gain and loss of satellite cell-derived myonuclei, and we captured the process of myonuclear migration. 55,56 Nuclear repositioning could be for the purpose of maintaining the 'myonuclear domain', 57,58 but could also be related to cytoskeletal rearrangement, 59,60 changes in innervation, 61,62 and/or blood vessel remodelling, 63 which may occur coincident with detraining. Nuclei are mechanosensors, [64][65][66] and myonuclear shape change could also be the consequence of alterations in transcriptional output.…”
Section: Discussionmentioning
confidence: 99%
“…It is a common feature of advanced cancer, caused by a combination of tumor-and host-derived factors, reduced food intake, and abnormal metabolism [123] (Figure 3). Recently, the involvement of neurogenic muscle atrophy was reported in a murine model of cancer cachexia [133], which may participate in muscle catabolism or metabolic reprogramming. Given that there is some controversy regarding this topic [134], further studies are needed to better define the involvement of compromised neuronal muscular junctions and muscle innervation in the progression of cancer cachexia.…”
Section: Skeletal Muscle Metabolism In Cancer Cachexiamentioning
confidence: 99%